PENGARUH TINGKAT PENGETAHUAN DAN MOTIVASI PERAWAT TERHADAP PENGGUNAAN APLIKASI SIMRS DI RUMAH SAKIT UMUM DAERAH SUMBAWA - David Haryanto; Zainuddin Zainuddin; Paris Ali Topan (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2023)
One of the service provided by the Hospital is by providing fast service, so give satisfaction to secoety. Service provided by the Hospital in increasing customer satisfactions whit using technology the SIMRS application. Contitution Republic of Indonesian No. 44 year 2019 about Hospital in chapter 1 paragraph 3 every Hospital must organize SIMRS application. The purpose of this study was to determine the effect of the level of knowledge and motivation of nurses on the use of the SIMRS application at RSUD Sumbawa. Population in this research were 149 respondents. The sampling technique in quantitative research with a sample of 109 respondent and the sampling technique in qualitative research with a sample of 10 respondent. The method on this research is a mix method with cross sectional and generic quality approach. The results of the study obtained a p-value 0,001 < 0,05% which means that there is an effect on level of knowledge nurses on the use of the SIMRS application and there is an influence on the motivation of nurses in using the SIMRS application at RSUD Sumbawa.